2021
DOI: 10.3390/en14217249
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Inverter Topology Using Diode Half-Bridge Circuit with Reduced Power Component

Abstract: This paper presents a new multilevel converter with a reduced number of power components for medium voltage applications. Both symmetric and asymmetric structures of the presented multilevel converter are proposed. The symmetric topology requires equal dc source values, whereas the asymmetric topology uses minimum switch count. However, both structures suffer from high blocking voltage across the switches. To reduce the blocking voltage on switches, an optimal topology is presented and analyzed for the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…However, this will lead to a decreased output RMS voltage. Also, in [16], an inverter is shown that can work at 9, 17, and 25 levels, but switching from nine levels to seventeen levels or to twenty five levels is not specified. Furthermore, in [16], the utilization of the MPPT technique with renewable energy sources is not done.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this will lead to a decreased output RMS voltage. Also, in [16], an inverter is shown that can work at 9, 17, and 25 levels, but switching from nine levels to seventeen levels or to twenty five levels is not specified. Furthermore, in [16], the utilization of the MPPT technique with renewable energy sources is not done.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Also, in [16], an inverter is shown that can work at 9, 17, and 25 levels, but switching from nine levels to seventeen levels or to twenty five levels is not specified. Furthermore, in [16], the utilization of the MPPT technique with renewable energy sources is not done. Accordingly, such techniques can be used with promising non-traditional renewable energy systems, such as thermoelectric modules [34], [35].…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A single-phase MLI with reduced switching stress on the power switches is suggested in [30]. A new MLI topology using a diode half-bridge circuit is explained in [31]. An MLI where the number of DC sources is reduced with the control of the switching scheme is suggested in [32].…”
Section: Introductionmentioning
confidence: 99%